Validitas dan Reliabilitas Instrumen Critical Thinking pada Pemanfaatan Media SIGUPIS di Sekolah Dasar - Diniarti, Noviroh; Sulianto, Joko (Universitas PGRI Semarang, 2023)
This development research aims to determine the validity and reliability of the critical thinking instrument for fifth grade elementary school students on the use of traditional game-based SIGUPIS media (Elementary Social Learning Song Creation). The assessment instrument developed was in the form of a questionnaire. The research subjects consisted of 3 validators and 20 fifth grade elementary school students. Data collection was carried out using a questionnaire or questionnaire technique. The data collected is in the form of data on the validity and reliability of critical thinking instruments. Data on the development of critical thinking instruments obtained through the validity test were analyzed with Aiken's v, while the data from the reliability test were analyzed with Kappa Statistics using SPSS version 16. The results showed that the validity test by the validator obtained the results of the ten statements used belonging to the high category so that the instrument is suitable for use. The reliability test shows that the alpha value is 0.967 so that the reliability of the instrument is included in the very high category. Based on the results of this study, the questionnaire instrument to find out the critical thinking of fifth grade elementary school students in utilizing SIGUPIS media based on traditional games is feasible to use.